Partisipasi Anggota Kelompok dalam Pengolahan dan Pemasaran Loloh Cemcem di Desa Wisata Penglipuran, Kabupaten Bangli, Provinsi Bali - CORNELLA FEBRINAULY SILITONGA; IGA. OKA SURYAWARDANI; I KETUT SURYA DIARTA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2019)
Participation of Group Members in Processing and Marketing of Loloh Cemcemin Penglipuran Tourism Village, Bangli Regency, Bali Province. Group participation in creating and developing local village food products is useful formaintaining the sustainability of local products and creating new jobs. LolohCemcemProduction Group of Penglipuran is one of groups that develops local villagefood products that have the potential to be developed and is able to create jobs.However, efforts in developing local products and increasing this group are also relatedto group membership that has relations in production, so that the group participation isexpected to be able to overcome the obstacles faced. The purpose of this study was todetermine the level of participation of group members in processing and marketing.The research location took place in Penglipuran Tourism Village, Bangli Sub-District,Bangli Regency. The analytical method used was descriptive statistical analysis.Theresults showed that the participation of group members in processing of Loloh Cemcemwas classified in the high category with a score of 69.72% with detailed indicators ofdecision making included reaching a score of 66.78%, implementation indicatorsreaching a score of 71.56%, the evaluation indicator reached a score of 59.58%, and theindicator of enjoying the results reached a score of 75.15%. The level of participation ofgroup members in the Loloh Cemcem marketing was in the low category with a score of58.51% with details on the decision-making indicators reaching a score of 55.93%, theimplementation indicator classified reached a score of 49.37%. The evaluation indicators reached a score of 60%, and the indicator of enjoying the results reached witha score of 68.75%.The suggestion that can be given to the group is that the participationof members in the group must be increased especially in loloh members are expected tobe more courageous in conveying ideas and suggestions in groups.